PERSEPSI DOSEN MENGENAI DAMPAK PEMBELAJARAN DARING SELAMA PANDEMI TERHADAP KEMAMPUAN BERBICARA BAHASA JEPANG PADA MAHASISWA - Nabela Silviani Oktavira; Merri Silvia Basri; Dini Budiani (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
This study examines the perception of professors of the impact of online learning on Japanese speaking ability. This study is a qualitative study of descriptive data taken using google forms from professors who have been able to teach Japanese language online or offline. The lecturer is from several universities located in Java and Sumatra. The reason for being a lecturer as a source is to know the abilities of online and offline students and the reflection of potion learning to speak Japanese online. Results show the faculty's perception of online students' speaking ability on aspects of vocabulary mastery, correct accent, and long or short vowel mention in vocabulary has a poor effect on online students. In terms of conversational intensity, speaking speed, and the influence of regional languages on Japanese pronunciation have a good effect on online students than offline students. Lecturer's reflection results lead students to provide supportive tools, provide more creative materials, use methods that attract attention, apply rules when learning online, include students in assessment, provide feedback and compliments on every learning. This study is expected to analyze the advantages and disadvantages of online learning as a reflection of subsequent learning. This study is expected to be an improvement in Japanese language learning in the future.